The image of hope in the work of Matnazar Abdulhakim (Zien Journal of Social Sciences and Humanities, 2022)
Only when people hope can they have a beautiful smile, endure trials, and endure hardships. Matnazar Abdulhakim also introduces the image of hope in poetry, saying that one should live with hope at all times.